The readiness of selected hotels in Malaysia to provide Muslim friendly services - Noor Najihah binti Mohd Daud (International Institute of Halal Research and Training, International Islamic University Malaysia, 2018)
This study aims at exploring the readiness of selected hotels in Malaysia towards adopting the standard of Muslim friendly services. It is conducted due to obscure terms used among hoteliers, different understanding as well as non-standardized implementation among them on the standard services. In addition, there are certain hoteliers even claimed their hotels as Muslim friendly or Islamic hotel, yet appropriate guidelines are not in place. In line with the establishment of the Malaysian Standard, MS2610:2015-Muslim Friendly Hospitality Services-Requirements, a need to explore the readiness of those hotels towards adopting and implementing Muslim friendly service is of paramount importance. In the study, the researcher identified three variables that determined those readiness, i.e.; the awareness and understanding of Muslim friendly concept among hoteliers, the management commitment and capability to fulfill the general as well as specific requirements of Muslim friendly services. Qualitative method comprised of interview with nine hotel staff, two representatives from policy maker and hotel owner association as well as observations were conducted to obtain an insight on the prescribed variables. The study found that the level of awareness among the hoteliers on the requirements of Muslim friendly services was at low level. On the other hand management commitment and capability to observe the requirement remain inadequate. For the specific requirements, these selected hotels are fully conformant, yet further support by the general requirements is still required. The study proposed, the importance of boosting further the awareness and understanding of the standard of Muslim friendly services among hoteliers, strengthening commitment of hotel management to the standard, and enhancing their capability towards implementation of Muslim friendly hotel services to comply with MS2610:2015.